Numerical study on the impact distance of a jet fire following the rupture of a natural gas pipeline. (November 2020) - Shan, Ke; Shuai, Jian; Yang, Guang; Meng, Wei; Wang, Chen; Zhou, Jixiang; Wu, Xu; Shi, Lei
Abstract: As a result of the catastrophic damage to society, the economy and the environment induced by pipeline fire and explosion accidents, determining the impact distance of a natural gas pipeline has attracted increasing attention. In this paper, first the impact distances of some typical natural gas pipeline fire and explosion accidents are statistically reviewed. Then, a 3D natural gas pipeline jet fire accident scenario model is established with FLACS software to simulate the entire dynamic process from gas leakage, diffusion, ignition to jet fire formation. The numerical results, such as the flame appearance, dimensions and thermal radiation, are compared with the experimental results in the literature, and very good agreement is obtained. Thereafter, a parametric study is performed by varying the pipe diameter, internal pressure, and wind speed. According to the thermal flux level, a method is proposed for determining the thermal radiation impact distance of a jet fire as a function of the internal pressure, pipe diameter and wind speed. This method provides technical support for risk assessment and accident consequence predictions for natural gas pipelines. Highlights: The impact distances of some typical natural gas pipeline fire and explosion accidents are statistically reviewed A 3D natural gas pipeline jet fire accident scenario model is established. A parametric study is performed by varying the pipe diameter, internal pressure, wind speed. A method is proposed for determining the thermal radiation impact distance of a jet fire.